Economic Impact of Refinements in ERAS Pathways in DIEP Flap Breast Reconstruction - Rodnoi, Pope; Teotia, Sumeet S.; Haddock, Nicholas T. (Journal of Reconstructive Microsurgery, 2021)
Introduction Enhanced recovery after surgery (ERAS) protocols at our institution have led to an expected decrease in hospital length of stay and opioid consumption for patients treated with deep inferior epigastric perforator (DIEP) flaps for breast reconstruction. We look to examine the economic patterns across these years to see the impact of costs for the patient and institution.Methods This study retrospectively evaluated consecutive patients treated with bilateral DIEP flaps for breast reconstruction between October 2015 and August 2020. We categorized the cases into three categories: pre-ERAS, ERAS, ERAS + bupivacaine. Primary outcomes observed included the contribution margin per operating suite case minute and total cost to the patient. An analysis of variance determined whether there was a difference between the three groups and a Tukey post-hoc analysis made pairwise comparisons. A p-value < 0.05 was significant.Results A total of 268 cases of bilateral DIEPs performed by the two senior authors were analyzed in this study. Seventy-four cases were pre-ERAS, 72 were ERAS, and 122 were ERAS + bupivacaine. There was a statistical difference between the contribution margin per operating minute. A Tukey post hoc test revealed that the average contribution margin per operating suite case minute was significantly higher for the ERAS and ERAS + bupivacaine compared with the pre-ERAS groups.There was a statistically significant difference between the total cost to the patients. A Tukey post hoc test revealed that the average total cost to the patient was statistically significantly lower for the ERAS and ERAS + bupivacaine compared with the pre-ERAS group.Conclusion Implementation of ERAS and continued improvements in ERAS resulted in significantly decreased costs for the patient and increased profitability for the hospital. Investing in improvements to ERAS protocols can improve profitability for the institution while simultaneously improving costs and access to care for patients in need of breast reconstruction.
Keywords: enhanced recovery after surgery; DIEP flap; economic impact